Experimental and theoretical investigation of powder-binder mixing mechanism for metal injection molding - Hossain, A.; Choudhury, I.A.; Nahar, N.; Hossain, I.; Bin Mamat, A. (2015)
Metallic powder and binder mixing mechanism plays a vital role in the quality of molded parts in metal injection molding. The present study is intended for experimental and theoretical investigation of powder-binder mixing mechanism to investigate the functional correlation among mixing parameters and performance characteristics for different composition of feedstocks. Powder loading and shear rate are considered as input parameter. Fuzzy expert system is adopted to test the validity of the experimental results by analyzing different numerical error criteria using the viscosity as output with respect to input parameters. The mean relative error and correlation coefficient for type A and type B were found to be 6.09 and 8.51 (<10) and 0.990 and 0.998, respectively. Hence the result indicates a reliable acceptability of the proposed amount of powder loading for feedstock preparation.